The Principle of Good Faith and Construction Disputes: a Study on Dispute Boards and Digital Transformation - Dharma Teguh Pribadi; Samian Samian; Sarwono Hardjomuljadi; Putra Amantha Hasibuan (International Journal Labs, 2025)
This study examines the application of the principle of good faith in Indonesian construction contracts, highlighting the challenges it faces due to the technical complexity, high uncertainty, and financial risks inherent in construction projects. While the principle is affirmed in Article 1338 paragraph (3) of the Civil Code, its practical application remains unclear, often leading to disputes over delays, compensation claims, and unclear obligations. In modern construction contracts, particularly those based on international standards like FIDIC, good faith is emphasized as an operational principle, with dispute resolution mechanisms like Dispute Adjudication Boards supporting collaboration and early dispute resolution. However, empirical studies show that these boards are sometimes used for strategic delays and selective disclosures, highlighting the tension between theoretical principles and practical behavior. The study also explores how digitalization, through technologies like Building Information Modeling, audit logs, and blockchain, transforms project monitoring and verification, offering opportunities to redefine good faith as an objective, verifiable principle. This research aims to assess the role of good faith in construction contracts, dispute boards, and digitalization, providing insights into how digital tools can help objectify and enforce good faith in Indonesian construction practices.